Effect of Inonotus obliquus (Fr.) Pilat extract on the regulation of glycolipid metabolism via PI3K/Akt and AMPK/ACC pathways in mice. (12th June 2021) - Zhang, Zhe; Liang, Xi; Tong, Lingjun; Lv, Youyou; Yi, Huaxi; Gong, Pimin; Tian, Xiaoying; Cui, Qingyu; Liu, Tongjie; Zhang, Lanwei
Abstract: Ethnopharmacological relevance: Inonotus obliquus (Fr.) Pilat is a mushroom belonging to the family Hymenochaetaceae. It is popularly called the Chaga mushroom in Russian folk medicine and has been used as a traditional medicine to treat diabetes mellitus in Eastern European and Asian countries. However, its effects on glycolipid metabolism disorders and underlying molecular mechanism of action remain unclear. Aim of the study: I. obliquus contains abundant functional components, which provide potential medicinal value. The purpose of this study was to investigate compositions of I. obliquus extract with a high-pressure water extraction method, and investigate the anti-type 2 diabetic effects of I. obliquus extract and the possible underlying mechanisms involved. Materials and methods: The I. obliquus was extracted by a high-pressure water extraction method, and tested its main components by special assay kit and instrumental analysis. Type 2 diabetic C57BL/6 mice were induced by high-fat diet with low-dose STZ injection, and were daily gavaged with different doses of I. o bliquus extract for 8 weeks. Glycemic, blood lipid profile, and histopathology of liver and pancreas were assessed. Underlying mechanisms related to glycemic control in liver were further performed. Results: The I. obliquus extract main compounds were β-Glucans, triterpenoids and polyphenol by determination. Oral administration of 250 mg/kg and 500 mg/kg I. obliquus extract significantly alleviated blood glucose and insulin resistance. Moreover, 250 mg/kg and 500 mg/kg of I. obliquus extract increased liver glycogen content and high-density lipoprotein cholesterol (HDL-C) levels while decreased total cholesterol (TC), triglyceride (TG) and low-density lipoprotein cholesterol (LDL-C) levels. Furthermore, the protein expression levels of phosphatidylinositol-3 kinase (PI3K), p-protein kinase B (Akt), p-adenosine monophosphate activated protein kinase (AMPK), and p-acetyl-CoA carboxylase (ACC) were upregulated, whereas sterol regulatory element-binding protein-1c (SREBP-1c) and fatty acid synthase (FAS) were downregulated after supplement with 250 mg/kg and 500 mg/kg of I. obliquus extract. Interestingly, I. obliquus extract was a dose-effect relationship within a certain range. 250 mg/kg had obvious anti-diabetes effect, and the effect of 500 mg/kg dose was the same as that of metformin. Conclusion: I. obliquus extract ameliorated insulin resistance and lipid metabolism disorders in diabetic mice. The hypoglycemic and hypolipidemic properties of I. obliquus extract were supposedly exerted via the regulation of the PI3K/Akt and AMPK/ACC signaling pathways. Graphical abstract: Image 1 Highlights: I. obliquus extract were extracted by a high-pressure water method. I. obliquus ameliorated insulin resistance and lipid metabolism disorders. The hypoglycemic mechanism of I. obliquus was PI3K/Akt signaling pathway. The hypolipidemia mechanism of I. obliquus was AMPK/ACC signaling pathway.